Development Strategy for Culture-Based Tourism Infrastructure on Serangan Island - Farhaeni, Mutria; Martini, Sri (Society, 2024)
This research analyzes the strategy for developing culture-based tourism destinations on Serangan Island. The method used was interviews with a purposive sampling approach to determine key informants. The research results show that the culture-based tourism destinations on Serangan Island are Sakenen Temple, As-Syuhada Mosque, Fisherman’s Village, Marine Tourism, and Turtle Breeding. Then, it was analyzed using SWOT analysis, where the results were that the Serangan Island tourism destination had a strong internal and external position because it could maintain its existing culture. An alternative strategy that can be implemented according to the current conditions of tourism destinations is the S-O strategy, meaning that the management of tourism destinations on Serangan Island can use its strengths to attract tourists. This study concludes that Serangan Island has cultural-based tourism destinations: Sakenan Temple, Asy-Syuhada Mosque, Fisherman’s Village, Turtle Conservation, and Marine Tourism. In addition, a SWOT analysis is needed to determine internal development strategies (strengths and weaknesses) and external development strategies (opportunities and challenges). Support is needed from the government and the private sector to facilitate, market, and support the surrounding community. Prohibition signs are needed to prevent environmental damage and pollution. Protection of customs, traditions, and arts and culture of the Serangan community through regional or village regulations. Better transportation access, such as piers, small bridges, or local transportation, supports visitor accessibility and comfort. Strengthening the marketing of Serangan Island as a cultural destination through social media and digital tourism platforms.